Efektivitas Konseling Kelompok Berbasis Cognitive Behavioral Therapy (CBT) dalam Mengatasi Kecemasan pada Remaja - Argina Farenta; Ghina Rizki Amalia; Nadia Nadia; Novi Fayza Widi Putantari; Ratna Sari Dewi (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
The issue of adolescent anxiety has become a serious concern as it can hinder their psychological, social, and academic development. One approach that can be used in group counseling is Cognitive Behavioral Therapy (CBT). This study aims to examine the effectiveness of applying Cognitive Behavioral Therapy (CBT) in group counseling to address adolescent anxiety. The research uses a literature review method, focusing on the results of Cognitive Behavioral Therapy (CBT) interventions in a group setting. The findings indicate that Cognitive Behavioral Therapy (CBT) is effective in reducing social anxiety, academic stress, and deviant behaviors. Techniques such as thought stopping, self-talk, and cognitive restructuring have proven to help change negative thought patterns into more adaptive or positive ones. In conclusion, group counseling based on Cognitive Behavioral Therapy (CBT) is an effective approach in helping adolescents manage anxiety in a healthy and productive way.